PENGARUH KOMUNIKASI INTERPERSONAL GURU DAN SISWA TERHADAP AKTIVITAS SISWA DI SMP NEGERI 4 PEKANBARU - Gema Putra Candra; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Interpersonal communication is communication taking place between two people who have an established relationship and clear. One of the processes of interaction with the environment that occurred in the process of learning is interpersonal communication that occurs between teachers and students. Students' learning activities are all activities performed in the process of interaction of teachers and students in order to achieve the learning objectives. The purpose of this study was to analyze the influence of interpersonal communication between teachers and students to student activities in SMP Negeri 4 Pekanbaru.The results of this study showed the influence of interpersonal communication between teacher and student to student activity at SMP Negeri 4 Pekanbaru. Interpersonal communication between teacher and student influence on the activity of students of SMP Negeri 4 Pekanbaru is 15.7 %, the remaining 84.3 % were caused by other factors from outside of this study . Therefore there is an influence between Interpersonal Communication Teacher and Student to Student Activities at SMP Negeri 4 Pekanbaru.